A Survey of Wireless Network Coding - Salah Abdulghani Alabady (Journal of engineering sciences and information technology, 2018)
Network coding (NC) over wireless networks has grown in recent years, so there is more attention from research community. NC is a technique that able to enhance the reliability and efficiency of network communications systems. Network coding has the capability to enable the intermediate nodes to combine and send out the received packets previously. NC has two main advantages: improvements in robustness and throughput. In this paper, a literature survey of network coding in a wireless environment is presented. We started by discussing the fundamental characteristics, advantage and disadvantage of network coding. Then we summarized the types of network coding and presented a literature review of network coding applications with routing protocol, throughput and delay modeling, MAC protocol and cross layer design.